1999
DOI: 10.1006/viro.1999.9928
|View full text |Cite
|
Sign up to set email alerts
|

Internal Initiation of Translation Directed by the 5′-Untranslated Region of the Tobamovirus Subgenomic RNA I2

Abstract: Previously we reported that, unlike RNA of typical tobamoviruses, the translation of the coat protein (CP) gene of a crucifer-infecting tobamovirus (crTMV) in vitro occurred by an internal ribosome entry mechanism mediated by the 148-nt region that contained an internal ribosome entry site (IRES(CP,148)(CR)). The equivalent 148-nt sequence from TMV U1 RNA (U1(CP,148)(SP)) was incapable of promoting internal initiation. In the present work, we have found that the 228-nt region upstream of the movement protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 36 publications
1
56
0
1
Order By: Relevance
“…Other plant RNA virus 5Ј UTRs have elements with IRES-like activity as assayed using dual-reporter constructs, but the limited length of the region upstream of initiation codons suggests that small-subunit entry differs from that of animal virus IRESs (3,22,24,25,31,41,54,60,69). 5Ј elements with IRES-like activity in TEV and BRV contain polypyrimidine sequences that are complementary to a region of 18S rRNA that is known to be accessible to base pairing with an mRNA template (24,25,54,69). This has led to suggestions that small IRES-like elements in plant viruses may act by attracting 40S subunits through cRNA-RNA interactions, similar to the case for prokaryotic Shine-Dalgarno sequences (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other plant RNA virus 5Ј UTRs have elements with IRES-like activity as assayed using dual-reporter constructs, but the limited length of the region upstream of initiation codons suggests that small-subunit entry differs from that of animal virus IRESs (3,22,24,25,31,41,54,60,69). 5Ј elements with IRES-like activity in TEV and BRV contain polypyrimidine sequences that are complementary to a region of 18S rRNA that is known to be accessible to base pairing with an mRNA template (24,25,54,69). This has led to suggestions that small IRES-like elements in plant viruses may act by attracting 40S subunits through cRNA-RNA interactions, similar to the case for prokaryotic Shine-Dalgarno sequences (53).…”
Section: Discussionmentioning
confidence: 99%
“…Many plant virus 5Ј UTRs contain translational enhancers (5Ј TEs) comprising pseudoknots, or pyrimidine-rich or purine-rich unstructured sequences, some of which can direct translation of internal open reading frames (ORFs) in bicistronic mRNAs, a hallmark of IRES activity (24,25,31,41,54,60,69). Cellular mRNAs that are translated when cap-dependent translation is inhibited also contain IRESs of limited size in their 5Ј UTRs (6,15,27,33,50).…”
mentioning
confidence: 99%
“…Recently, a new tobamovirus [cruciferinfecting tobamovirus (crTMV)] capable of systemically infecting members of the Brassicaceae family has been isolated and characterized (21). We reported that the 148-nt region upstream of the CP gene of crTMV RNA contains an IRES (IRES CP,148 CR ), promoting cap-independent and internal translation of the CP gene and different reporter genes from dicistronic constructs (22,23). Recently, the ability of IRES CP,148 CR to promote internal translation was confirmed in a potato virus X vector-based system (24 CR exhibited a high capacity to mediate translation of the 3Ј-proximal ␤-glucuronidase (GUS) gene located on a dicistronic transcript in all of the types of cells tested.…”
mentioning
confidence: 99%
“…In particular, an IRES element derived from the coat protein gene of the crucifer Tobacco Mosaic Virus (cr-TMV) has been used for polycistronic gene expression in plants (Ha et al 2010;Skulachev et al 1999). Yamamoto et al used the cr-TMV IRES to selectively express a firefly luciferase gene from a single mRNA that also encoded a Renilla luciferase gene positioned 5′ to the firefly gene (Yamamoto et al 2003).…”
mentioning
confidence: 99%